THE PROBLEM OF CASTE WITHIN THE CHURCH - Raja, Jebamalai (Journal of Dharma, 1999)
Has conversion to Christianity decastified the converts? Theoretically it has to. The Christian tenets militate against persons professing Christian faith being divided or discriminated on the basis of any such classification as the caste system. But de facto, the Christian churches, be it Catholic or Protestant, are known for their discrimination against the Dalit Christians. In a memorandum submitted to the Simon Commission in 1930 the converts from the Untouchable Community have expressed their disappointment with the Christian Churches, "Though the operation of several factors, the more important of them being the strong caste retaining Hindu mentality of the converts to Christianity, and the indifference powerlessness and apathy of the Missionaries, we remain today what we were before we become Christians-Untouchables-degraded by the laws of social position obtaining in the land, rejected by caste Christians, despised by Caste Hindus and excluded by our Hindu deprrsseed Class brethren.